ALGORITHMIC SOFTWARE TASK OF RESTORING THE FULL ANGULAR VELOCITY IN A STATIONARY FIELD - Коврижкін, І. О. (Science-based technologies, 2014)
The method of determination of corners of spatial orientation of aircraft is examined at the use of signals of the system of satellite navigation and magnetometer sensors. A method is proposed for use in systems with micromechanical gyroscopic sensors for small classes drones. This is an approach of building a system of periodic correction of angles spatial orientation of UAV based on data measuring the earth's magnetic field. It should be noted that the error can be significantly less than 1 ° on straight sections of the flight, as these are the main areas and are assumed for making a correction. The basic performance of the proposed approach was tested in the test field trials. To implement the above approach author used magnetometer triad KMZ-10